2015
DOI: 10.1038/srep11599
|View full text |Cite
|
Sign up to set email alerts
|

Heparin interacts with elongation factor 1α of Cryptosporidium parvum and inhibits invasion

Abstract: Cryptosporidium parvum is an apicomplexan parasite that can cause serious watery diarrhea, cryptosporidiosis, in human and other mammals. C. parvum invades gastrointestinal epithelial cells, which have abundant glycosaminoglycans on their cell surface. However, little is known about the interaction between C. parvum and glycosaminoglycans. In this study, we assessed the inhibitory effect of sulfated polysaccharides on C. parvum invasion of host cells and identified the parasite ligands that interact with sulfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 54 publications
0
25
0
Order By: Relevance
“…Recently, Inomata and colleagues reported that sulfated GAGs inhibit C. parvum infection in a dose-dependent manner (24). They also demonstrated binding of heparin to elongation factor 1␣, an adhesin previously implicated in the mediation of C. parvum invasion in vitro (49).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Recently, Inomata and colleagues reported that sulfated GAGs inhibit C. parvum infection in a dose-dependent manner (24). They also demonstrated binding of heparin to elongation factor 1␣, an adhesin previously implicated in the mediation of C. parvum invasion in vitro (49).…”
Section: Discussionmentioning
confidence: 98%
“…(18,19), and Toxoplasma gondii (20)(21)(22)(23). Recently, Inomata et al reported that heparin mediates C. parvum invasion in vitro via interaction with elongation factor 1␣ (24). Still, the precise role of GAGs during C. parvum infection and the mechanisms underlying these interactions are poorly understood.…”
mentioning
confidence: 99%
“…In bacteria, heparin-binding hemagglutinin (HBHA) in Mycobacterium [7][8][9] , the Fim2 subunit of fimbriae in Bordetella pertussis 10) , and many proteins including metabolic enzymes from Mycoplasma 11) and Staphylococcus aureus 12) have been identified. Among eukaryotic pathogens, heparinbinding motifs in proteins from Candida have been described 13) , as have a Blastomyces adhesin-1 called BAD-1 14) and other heparin-interacting proteins, including an elongation factor of Cryptosporidium 15) . Many of these proteins may have roles in adherence, biofilm formation, invasion, or stress responses.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, cells deficient in heparan sulfate show less susceptibility to invasion. It is as if you needed a sulfated key and a sulfated lock to open the door [42,43]. Artemisia annua contains 0.4 % of sulfur which is much higher than in most plants [44].…”
Section: New Insights Into Malaria Prophylaxis 3/5mentioning
confidence: 99%